Canadian North aircraft -- photograph ... - Seale, Linda N. (University of Alberta Library, 2012)
Canadian North is a northern aboriginal owned airline based in Yellowknife and serving Arctic Canada. This aircraft at Yellowknife Airport has the airline logo which includes a polar bear, the midnight sun and the Northern Lights (aurora borealis). The aircraft is a Boeing 727, the largest plane usually flown in the Arctic because of ifs fuel capacity for long distance flights between settlements. Many 727s are 'combis' -- a combination of passenger and cargo capacity. Photograph taken March 2012. ...